2016
DOI: 10.1016/j.jaci.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Novel vaccines targeting dendritic cells by coupling allergoids to nonoxidized mannan enhance allergen uptake and induce functional regulatory T cells through programmed death ligand 1

Abstract: Allergoids conjugated to nonoxidized mannan represent suitable vaccines for AIT. Our findings might also be of the utmost relevance to development of therapeutic interventions in other immune tolerance-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
150
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(157 citation statements)
references
References 60 publications
(103 reference statements)
5
150
0
2
Order By: Relevance
“…We previously demonstrated that PM‐allergoids are much better captured than native allergens by human16 and canine17 DCs and that this property is lost upon mannan oxidation. Here we show that this is also the case in mice when assessing antigen‐presenting cells (CD45 + MHC‐II + ) from the sublingual mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that PM‐allergoids are much better captured than native allergens by human16 and canine17 DCs and that this property is lost upon mannan oxidation. Here we show that this is also the case in mice when assessing antigen‐presenting cells (CD45 + MHC‐II + ) from the sublingual mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…N, PM, and PM‐OX allergen preparations were equally labeled with Alexa 488 maleimide (Thermo Fisher Scientific) and allergen uptake performed as described 16. Briefly, cells (3 × 10 5 ) were incubated (30 minutes at 37°C) with 100 μg/mL of each labeled preparation in RPMI.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations